Role of happiness belief: mediating lying flatism and attitudes toward singlehood - Heng, Zeng Qing; Chin, Joey (2021)
The number of singlehood is rising gradually in Malaysia, while lying flatism, a new emerging life attitude in which individuals refused to participate in consumerist lifestyles, is anticipated to affect the attitudes toward singlehood through the mediation of the individuals’ belief that happiness can be achieved without romantic relationships (happiness belief). Therefore, this study is to examine the mediating effect of happiness belief between lying flatism and attitudes toward singlehood. Quantitative cross-sectional research was adopted with 232 participants recruited through purposive and snowball sampling methods among single Malaysian aged between 18 to 24. Qualtrics questionnaire which consisted of nine sections was distributed online. The sections were demographic data, questionnaires of control variables – Negative Stereotyping of Single Persons (NSSP) and Fear of Being Single (FBSS), a pre-manipulation single item for feelings toward lying flatism, essay for manipulation, a post-manipulation single item for feelings toward lying flatism, single item for Happiness Belief (HB), Attitudes toward Singlehood Scale (AtSS), identification of participants for the token of appreciation, and debriefing. With gender, singlism and fear of being single being controlled, the present study shows that there were significant relationships found between feelings toward lying flatism, happiness belief and attitudes toward singlehood. Happiness belief was found to be positively correlated with attitudes toward singlehood. It also supported to mediate the relationship between feelings toward lying flatism and attitudes toward singlehood. Findings in this study can be contributed to the possible reason for individuals’ attitudes toward singlehood.